2023
DOI: 10.36348/sijll.2023.v06i02.004
|View full text |Cite
|
Sign up to set email alerts
|

Saudi University Learners’ Metacognitive Abilities and Writing Performance

Abstract: Metacognitive knowledge, knowledge about knowledge, was found to have a positive effect on learners’ performance, self-regulation, and academic success (Hartman, 2001; Wenden, 2001 & McCormick, 2013). However, little research has been done about the use of metacognitive knowledge and strategies applied in EFL writing in a Saudi context. The present study investigated the university learners’ metacognitive abilities in relation to writing including other variables like learners’ educational background and y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, the underlying factors responsible for these gender differences require further investigation. Previous studies have found that females tend to exhibit higher levels of metacognitive awareness than males (Basaffar & Bukhari, 2023;Collins et al, 2021;Farahian, 2017;. However, the reasons for these gender differences remain unclear and require further investigation (Alhaqbani & Riazi, 2012;Alodwan & Ibnian, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the underlying factors responsible for these gender differences require further investigation. Previous studies have found that females tend to exhibit higher levels of metacognitive awareness than males (Basaffar & Bukhari, 2023;Collins et al, 2021;Farahian, 2017;. However, the reasons for these gender differences remain unclear and require further investigation (Alhaqbani & Riazi, 2012;Alodwan & Ibnian, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…This approach can help students gain insight into their own writing processes and identify areas for improvement, ultimately resulting in more effective writing (Chamot, 2005;Liu et al, 2022;Utkina, 2022). However, research on the application of metacognitive knowledge and strategies in EFL writing for Saudi Arabian students is limited (Basaffar & Bukhari, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that the learners graduating should be ready with the necessary abilities for critical thinking and performing an efficient role in society, which indicates that they should be able to process their language skills as a medium for them to form connections and support their global socio-economic ties (Hooker & Kim,2019;Kannan & Munday, 2018;Khuraisah, Khalid, & Husnin, 2020;Basaffar & Bukhari, 2023). According to Samans and Zahid (2017), there is no balance between the required skills and the existing skills in the MENA region which means that the 21st Century learners lack the abilities required for current or future jobs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4IR is unlocking potential opportunities for the region, and the region needs to make the right decisions "… in reforming education broadly, upskilling and reskilling large cohorts of the population and preparing labor policy for the changes to come…" (Samans & Zahid, 2017, p. 2). Thus, the primary role of EFL in the region is 'upskilling and reskilling', and the learners need abilities to examine what the real world unfolds to them (Basaffar & Bukhari, 2023). Language should function as a tool for learners to communicate their thoughts, deal with the rapidly changing global and local socio-economic systems, and navigate through the diversified challenges of life (Pauceanu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation